When ignorance is bliss: theory and experiment on collective learning (2017)
When do groups and societies choose to be uninformed? We study a commit-tee that needs to vote on a reform which will give every member a private state-dependent payoff. The committee can vote to learn the state at no cost. We show that the committee decides not to learn the state when preferences are more fractionalised on the state-relevant dimension than on the state-irrelevant dimension. Hence, decisions on divisive issues are likely to be made in haste, and heterogeneous societies tend to seek less information. A simple laboratory experiment confirms key results.